Comparison between ticagrelor versus clopidogrel in long term outcomes of Taiwanese diabetic subjects with acute coronary syndrome undergoing successful revascularization: From TSOC ACS-DM registry. Issue 19 (May 2020) - Wang, Cheng-An; Hsieh, Yi-Chen; Huang, Chun-Yao; Liu, Ju-Chi; Hsieh, Ming-Hsiung; Lin, Yung-Kuo; Yeh, Jong-Shiuan
Abstract : Abstract: Although previous clinical trials demonstrated that ticagrelor could reduce cardiovascular events and mortality versus clopidogrel in patients with acute coronary syndrome (ACS), the real-world evidence of its clinical impacts on East Asian Diabetic population has rarely been investigated. Between November 2013 and June 2015, 1534 patients were recruited into the Acute Coronary Syndrome-Diabetes Mellitus Registry of the Taiwan Society of Cardiology (TSOC ACS-DM registry). After propensity score matching, a total of 730 patients undergoing successful revascularization and discharged on ticagrelor (N = 365) or clopidogrel (N = 365) were analyzed. The primary and secondary endpoints were all-cause mortality and re-hospitalization, respectively. The all-cause death associated with ticagrelor vs clopidogrel was 3.6% vs 7.4% (adjusted hazard ratio (HR) 0.34 [0.15–0.80]; P  = .0138) at 24 months. The re-hospitalization rate at 24 months was 38.9% vs 39.2% ( P  = .3258). For diabetic patients with ACS, ticagrelor provided better survival benefit than clopidogrel without an increase of re-hospitalization in 24 months after successful percutaneous coronary intervention. This study in real-world circumstance provided valuable complementary data to externally validate platelet inhibition and patient outcomes (PLATO) finding especially in Asian diabetic population.